Abrasive wear performance of untreated SCF reinforced polymer composite - ELTAYEB, N (ELSEVIER SCIENCE SA, 2008)
This work aims to present a study on abrasive wear behaviour of polymer reinforced with natural fibre. Specifically, untreated sugarcane fibre (SCF) was used in two forms to reinforce polyester (SCRP). Chopped SCFs with different lengths (1, 5, 10mm) randomly dispersed (C-SCRP) and continuously unidirectional fibres (U-SCRP) with two different orientations were prepared using hand-lay up and closed mould techniques. Despite the good adhesion between fibre and matrix, results of mechanical tests showed poor tensile strength of SCRP composite. This was attributed to the weak site inside the fibre itself which could not bear the stress transfer from matrix via the fibre. Experimental results of abrasive wear tests revealed that wear of SCRP composite was sensitive to variations of load, fibre length and fibre orientation and less sensitive to sliding velocity In C-SCRP composite, the lowest wear resistance was observed for composite with 1 mm fibre length as the fibres had no support and removed easily with minimum resistance to the action of abrasive particles followed by 10 and 5 mm fibre length. Meanwhile, C-SCRP composite with 5 mm fibre length offered the highest resistance to material removal compared to the other fibre length used. In U-SCRP composite, the anti-parallel-orientation (APO) exhibited better wear performance compared to the parallel-orientation (PO) one. The predominant wear mechanisms in the case of C-SCRP composite were plastic deformation, micro-cutting, pitting in the matrix, and fibre removal. In the case of U-SCRP composite in (PO) wear mechanisms were micro-cutting, ploughing, fragmentation of wear debris in the matrix and excessive deterioration of fibre surface followed by delamination, while in (APO) the wear mechanisms were micro-cutting in the resin matrix and tearing the fibre transversely at their ends. (c) 2008 Elsevier B.V. All rights reserved.